Tensions and paradoxes in electronic patient record research: a systematic literature review using the meta-narrative method. - Greenhalgh, T; Potts, H; Wong, G; Bark, P; Swinglehurst, D (2009)
CONTEXT: The extensive research literature on electronic patient records (EPRs) presents challenges to systematic reviewers because it covers multiple research traditions with different underlying philosophical assumptions and methodological approaches. METHODS: Using the meta-narrative method and searching beyond the Medline-indexed literature, this review used "conflicting" findings to address higher-order questions about how researchers had differently conceptualized and studied the EPR and its implementation. FINDINGS: Twenty-four previous systematic reviews and ninety-four further primary studies were considered. Key tensions in the literature centered on (1) the EPR ("container" or "itinerary"); (2) the EPR user ("information-processer" or "member of socio-technical network"); (3) organizational context ("the setting within which the EPR is implemented" or "the EPR-in-use"); (4) clinical work ("decision making" or "situated practice"); (5) the process of change ("the logic of determinism" or "the logic of opposition"); (6) implementation success ("objectively defined" or "socially negotiated"); and (7) complexity and scale ("the bigger the better" or "small is beautiful"). CONCLUSIONS: The findings suggest that EPR use will always require human input to recontextualize knowledge; that even though secondary work (audit, research, billing) may be made more efficient by the EPR, primary clinical work may be made less efficient; that paper may offer a unique degree of ecological flexibility; and that smaller EPR systems may sometimes be more efficient and effective than larger ones. We suggest an agenda for further research.